Stabilized leachates: sequential coagulation–flocculation + chemical oxidation process - Javier Rivas, F. (2004)
The combined sedimentation-chemical oxidation treatment of medium-stabilized landfill leachates has been investigated. The sequence of stages implemented was: (a) coagulation–flocculation by pH decrease (pH 2) to acidic conditions (COD removal ≈ 25% related to COD0 ≈ 7500 ppm); (b) coagulation–flocculation by Fe(III) addition (0.01 M) at pH 3.5 (COD removal ≈ 40% related to COD of supernatant after step (a); (c) Fenton (Fe(III) = 0.01 M; H2O2 = 1.0 M) oxidation (COD removal ≈ 80% related to COD of supernatant after step (a); and (d) coagulation–flocculation of Fenton’s effluent at pH 3.5 (COD removal ≈ 90% related to COD of supernatant after step (a). The use of Kynch theory allows for the design of clarifiers based on the amount of solids fed. For a general example of 1000 m3 day−1 of a feeding stream, clarifier area values of 286, 111 and 231 m2 were calculated for compacting indices of 3.7, 2.67 and 2.83 corresponding to the first, second and third consecutive sedimentation processes, respectively, (steps (a), (b) and (d)).